Insights on Academic Integrity Policy Development: Crafting Policy Catered to Your Institution - Al-Haque, Rashed (Canadian Perspectives on Academic Integrity, 2021)
The purpose of this session is to highlight the opportunities and challenges of crafting an academic integrity policy that is responsive to an institution’s unique needs and character. A robust and comprehensive policy is crucial to upholding the values and principles of academic integrity within higher education. Over the course of two years (2018-2020), Camosun College’s Office of Education Policy and Planning worked with stakeholders from across the college to develop its new academic integrity policy and procedures. The work led to an extensive overhaul of the college’s academic integrity policy along with a review of its associated procedures intended to address and appeal allegations of academic misconduct. The end result is a clear policy and set of procedures that appropriately balances the rights and responsibilities of students, faculty, and administration. The presentation will focus on sharing strategies on how to engage institutional stakeholders in a meaningful way to develop an academic integrity policy for your college/university. Emphasis will also be placed on what supports and resources are required to implement an academic integrity policy and insights from how policy implementation is going so far at Camosun.